Factors Predicting Perception of Insufficient Milk Supply in First-time Postpartum Mothers - Laphon, Suwanan; Sangin, Siriwan; Wacharasin, Chintana (Nursing Science Journal of Thailand, 2025)
Purpose: To study predictive factors for the perception of insufficient milk supply in first-time postpartum mothers. Design: Predictive research design. Methods: The sample consisted of 135 first-time postpartum mothers who received postnatal check-ups 4-6 weeks after delivery at the outpatient department of a tertiary hospital, affiliated with Bangkok Metropolitan Administration. Data was collected using a questionnaire on perceived insufficient breast milk, a questionnaire on family support for breastfeeding, an infant temperament questionnaire for infants aged 1-3 months, a breastfeeding knowledge questionnaire, and a breastfeeding self-efficacy questionnaire. Data were analyzed using descriptive statistics and enter multiple regression analysis. Main findings: First-time postpartum mothers had perceived insufficient milk supply ( = 48.05, SD = 15.60) at a low level. The factors that could significantly predict the perceived insufficient milk supply among first-time postpartum mothers at significance level .05 were: breastfeeding self-efficacy ( = - .32), breastfeeding knowledge ( = - .23), supplementing feeding ( = - .22), family support for breastfeeding ( = - .17), education level ( = - .15), and infant temperament ( = - .11). All of the study factors could account for 75% of the variance explained in perceived insufficient milk supply among first-time postpartum mothers (R2 = .75). Conclusion and recommendations: Nurses should assess these predicting factors and operate them as nursing interventions to promote the perception of adequate milk production among first-time postpartum mothers.